Implementation of Kentucky Nongraded Primary Program - Kannapel et al, Patricia J.; Aagaard, Lola; Coe, Pamelia; Reeves, Cynthia A. (Education Policy Analysis Archives, 2000)
We examine the development of the Kentucky nongraded primary program at the state level, and in six rural elementary schools from 1991 through 1998 (case studies of four of these schools are included in Appendix A). Data collected from our longitudinal qualitative study reveal that teachers changed their classrooms in response to the primary program mandate, and some positive outcomes occurred for students. Implementation was hampered, however, by rapid implementation timelines, failure to clearly articulate the purpose of the program and how it linked with a larger reform effort, and a firmly entrenched "graded" mindset. Currently, progress toward full implementation of a continuous progress model for primary students has stagnated. To revive the program, policymakers need to make program goals clear, demonstrate how its implementation will facilitate attainment of reform goals, and assist teachers in implementing the program as intended. (Note 1)